2018
DOI: 10.1002/lsm.23023
|View full text |Cite
|
Sign up to set email alerts
|

The toxic edge—A novel treatment for refractory erythema and flushing of rosacea

Abstract: Purpose Rosacea is a common, chronic facial skin disease that affects the quality of life. Treatment of facial erythema with intradermal botulinum toxin injection has previously been reported. The primary objective of the study was the safety and efficacy of thermal decomposition of the stratum corneum using a novel non‐laser thermomechanical system (Tixel, Novoxel, Israel) to increase skin permeability for Botulinum toxin in the treatment of facial flushing of rosacea. Methods A retrospective review of16 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 49 publications
(73 reference statements)
0
65
2
1
Order By: Relevance
“…These effects allow the penetration of topically applied Botulinium toxin into the skin through the stratum corneum. This system has already been demonstrated to significantly increase the permeability of a couple of topically applied medications including, lidocaine (Sintov & Brandys‐Sitton, ) and as proved by Friedman et al also Botulinium toxin (which was used in severe cases of rosacea; Friedman et al, ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These effects allow the penetration of topically applied Botulinium toxin into the skin through the stratum corneum. This system has already been demonstrated to significantly increase the permeability of a couple of topically applied medications including, lidocaine (Sintov & Brandys‐Sitton, ) and as proved by Friedman et al also Botulinium toxin (which was used in severe cases of rosacea; Friedman et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…This effect and the subsequent decrease of microorganism colonization might serve as one explanation for its efficacy in the treatment of Hailey–Hailey disease (Benohanian, ). Botulinum toxin cannot cross the stratum corneum, therefore, its injection is required for both the treatment of hyperhidrosis (de Almeida & Montagner, ; Glaser & Galperin, ) and for the treatment of Hailey–Hailey disease (Charlton et al, ; Friedman et al, ; Kothapalli & Caccetta, ; Lapiere et al, ). It is an effective treatment but a painful, expensive, and the duration effects is for several months only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides skin ablation, TMA causing a low‐energy thermal decomposition of the stratum corneum can enhance the transepidermal penetration of substances 6; recently proved for botulinum toxin and 5‐amino‐levulinic‐acid 12,13. These findings, showing an increased permeability of the epidermis after TMA, could maybe be extrapolated for aesthetic applications, like platelet‐rich‐plasma treatments.…”
Section: Discussionmentioning
confidence: 93%
“…This study further substantiates the evidence introduced by earlier studies of low‐energy TMFI pretreatments for PDD. Friedman et al reported treatment of rosacea with botulinum toxin following TMFI pretreatment, and Sintov et al described the permeation of several hydrophilic molecules after TMFI pretreatment in an ex vivo study.…”
Section: Discussionmentioning
confidence: 99%